Effectiveness of Emotion-Focused Therapy on Self-Efficacy and Posttraumatic Growth in Women with Breast Cancer - Torabiyan, Atena; Gholipour, Masoumeh; Yektaparast, Samaneh; Ghodsi, Bahar; Tarnas, Ghazaleh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to examine the effectiveness of emotion-focused therapy on self-efficacy and posttraumatic growth in women with breast cancer.Methods:  This quasi-experimental study (pre-test - post-test with control group) involved 30 women with breast cancer in Sari (2021) who were selected through purposive sampling and randomly assigned into two groups of 15 participants each, an experimental group and a control group. The measurement instruments used were the General Self-Efficacy Scale by Schwarzer and Jerusalem (1979) and the Posttraumatic Growth Inventory by Tedeschi and Calhoun (1996), completed by the participants. Subsequently, participants in the experimental group attended 10 sessions of 60-minute emotion-focused therapy over a period of ten weeks. However, no therapy sessions were conducted for the control group. Ultimately, data analysis was performed using the covariance analysis method.Findings:  The analysis revealed that after the intervention, there was a significant difference between the control and experimental groups in both variables of self-efficacy and posttraumatic growth (p ≤ .05). Significant differences were observed in the components of self-efficacy (general self-preparedness and social self-efficacy) and three components of posttraumatic growth (relating to others, personal strength, and appreciation of life) between the women in the experimental and control groups (p ≤ .05); however, no significant differences were observed in the components of new possibilities and spiritual change.Conclusion:  The use of emotion-focused therapy is an appropriate intervention to enhance self-efficacy and posttraumatic growth in women with breast cancer, which can be beneficial for improving psychological well-being and better coping with the disease and treatment.